Are First Trimester Nuchal Septations Independent Risk Factors for Chromosomal Anomalies?. (28th November 2016) - Mack, Lauren M.; Lee, Wesley; Mastrobattista, Joan M.; Belfort, Michael A.; Van den Veyver, Ignatia B.; Shamshirsaz, Alireza A.; Ruano, Rodrigo; Sanz Cortes, Magdalena; Espinoza, Andres; Thiam Diouf, Arame; Espinoza, Jimmy
Abstract : Objectives: There is conflicting information regarding the role of nuchal septations during first‐trimester genetic screening. This study was designed to determine whether nuchal septations are risk factors for chromosomal anomalies, independent of increased nuchal translucency (NT), in the first trimester of pregnancy. Methods: This retrospective cohort study included all women who underwent first‐trimester genetic screening between November 2011 and December 2014. The 95th percentile for the NT measurement was calculated for each gestational week. A multivariable logistic regression analysis was performed to determine whether the visualization of nuchal septations was an independent risk factor for chromosomal analysis while controlling for confounding variables. P  < .05 was considered significant. Results: Chromosomal abnormalities were present in 1.0% of the population (33 of 3275). The prevalence of chromosomal abnormalities was significantly higher among fetuses with nuchal septations compared to fetuses with normal NT without septations ( P  < .001) and those with NT above the 95th percentile without septations ( P  < .001). The sonographic evidence of septations was associated with high risk of chromosomal abnormalities (odds ratio, 40.0; 95% confidence interval, 9.1–174.0) after controlling for NT measurements and other confounding variables. Conclusions: Visualization of nuchal septations during first‐trimester genetic screening is a powerful risk factor for chromosomal anomalies, independent of increased NT.